Ensuring Nutritional Security for Better Health - Wang, Weiqun (My University, 2016)
Nutrition as a science deals with the interpretation of the interaction of nutrients in growth, reproduction, health, maintenance, and disease of an organism, that includes intake, absorption, assimilation, catabolism and excretion of dietary factors. Nutrition and food science is an international open access journal that publishes scientific articles related to food sciences and nutrition. The current volume no. 6, issue 3 published nine research articles, six review articles along with mini review and commentary articles.
Citation: Wang WG (2016) Ensuring Nutritional Security for Better Health. J Nutr Food Sci 6:e125. doi:10.4172/2155-9600.100e125